ICTV Virus Taxonomy Profile: Pseudoviridae. (2nd March 2021) - Llorens, Carlos; Soriano, Beatriz; Krupovic, Mart; ,
Abstract : Pseudoviridae is a family of reverse-transcribing viruses with long terminal repeats (LTRs) belonging to the order Ortervirales . Pseudoviruses are commonly found integrated in the genomes of diverse plants, fungi and animals and are broadly known as Ty1/Copia LTR retrotransposons. Inside the cell, they form icosahedral virus particles, but unlike most other viruses, do not have an extracellular phase. This is a summary of the ICTV Report on the family Pseudoviridae, which is available at ictv.global/report/pseudoviridae .